Writing Democracy - Karen Gammelgaard, Eirik Holmøyvik (Berghahn Books, 2014)
In 2014, the Norwegian Constitution has existed for two hundred years. Adopted on 17 May 1814, it is the oldest functioning constitution in Europe. Only the US Constitution (adopted in 1787) is older. The beginnings of the Norwegian Constitution, as well as its longevity, have been accompanied by dramatic events, including the breakup of the long-lasting union with Denmark in early 1814, war with Sweden (summer 1814), union with Sweden (1814–1905), German occupation (1940–1945), and two referenda on Norway’s place in European cooperation structures (1972 and 1994). All these events have been topics of comprehensive research and will indisputably continue to be so. This volume’s authors, however, take a different approach. Rather than focusing on events, they focus on practices connected with putting the Constitution into text, with setting down in a document the rules of government and human rights, and with interpreting that document. These practices may lack palpable outward dramatics because they most often take place in forums— conference rooms, meeting rooms, studies—where the drama of conflicting interests occurs not as physically tangible fights but in represented shape only: as words, sentences, and paragraphs. The lack of outward drama is also caused by the fact that textual practices often concern political decisions on a micro level (Chilton 2004: 4). Such practices have the character of everyday, often meticulous, work. Nonetheless, these easily overlooked practices, and not least the sum of many such practices, may have consequences as significant as actions unfolding on real battlefields. In many ways, these textual practices lie at the heart of a well-functioning democracy. It is the shared recognition of textual practices’ significance that sparked this volume’s authors to scrutinize practices that relate to the Norwegian Constitution as a text.